(1 →3)- β -D-Glucan and endotoxin modulate immune response to inhaled allergen. Issue 2 (1998) - Rylander Rylander, R. R.; Holt Holt, P. G. P. G.
Abstract : Exposure to dust may involve co-exposure to agents which are allergens, together with those which are pro-inflamm atory. To study the effects of such a coexposure, the humoral and inflammatory responses were studied in guinea pigs inhaling the T-cell dependent antigen ovalbumin (OVA) and the inflammatory agents( 1 → 3 ) -β -D-glucan and lipopolysaccharide (LPS). The effects were evaluated as inflammatory cells in the lung and serum antibodies to OVA. LPS caused a stimulation of the OVA-induced antibody production which was abolished by simultaneous exposure to( 1 → 3 ) -β-D-glucan. An increase of eosinophils after OVA exposure was decreased by coexposure to( 1 → 3 ) -β-D-glucan. The results demonstrate a complex interaction between adaptive and innate immune mechanisms in the lung, determined by exposure to common contaminants in airborne dust.